Effectiveness of nanoparticles solutions and conventional endodontic irrigants against Enterococcus faecalis biofilm - Josiane de Almeida; Bruna Casagrande Cechella; Anarela Vassen Bernardi; Andrea de Lima Pimenta; Wilson Tadeu Felippe (Wolters Kluwer Medknow Publications, 2018)
Context: To overcome the challenge imposed by the presence of biofilm and reach significant bacterial reduction of the root canals, many irrigants have been indicated during endodontic treatment, among them nanoparticles solutions. Aims: This study aims to evaluate the effectiveness of experimental solutions containing silver and zinc oxide nanoparticles (ZnO Np) and conventional endodontic irrigants against Enterococcus faecalis biofilm, in root canals. Methods: Seventy-six extracted human teeth were biomechanically prepared and sterilized. The root canal surface was exposed to E. faecalis suspension to form a 7-day-old biofilm. Four teeth were analyzed by scanning electron microscopy (SEM) to confirm the presence of biofilm. The remaining teeth were randomly divided into 6 groups (n = 12) and treated with passive ultrasonic irrigation and different solutions: G1 - 0.85% saline (control); G2 - 2% chlorhexidine gluconate (CHX); G3 - 5% sodium hypochlorite (NaOCl); G4 - 1% NaOCl; G5 - 1% silver nanoparticles (Ag Np) solution; and G6 - 26% ZnO Np solution. The susceptibility of E. faecalis biofilms to disinfecting solutions (n = 10) was determined by quantification of colony-forming units. SEM analysis was also carried out to examine the biofilm structure after treatments (n = 2). Data were analyzed by Kruskal-Wallis and Dunn post hoc tests (P < 0.05). Results: All tested solutions showed superior effectiveness compared to 0.85% saline (P < 0.05). Overall, 2% CHX presented the most effective action against E. faecalis biofilm, followed by 5% NaOCl, 1% Ag Np, 26% ZnO Np, and 1% NaOCl. Conclusions: 1% Ag Np and 26% ZnO Np were effective against E. faecalis biofilm similarly to conventional endodontic irrigants.